Mengintegrasikan Nilai-Nilai Pendidikan Multikultural Dalam Pembelajaran Pendidikan Agama Islam di SMPN 8 Palangka Raya - Zaini, Muhammad; Normuslim, Normuslim; Zulkarnain, Ali Iskandar (Jurnal Ilmiah Global Education, 2025)
Indonesia, a nation rich in ethnic, religious, cultural, and tribal diversity, faces both challenges and opportunities in building national integration. Islamic Religious Education (IRE) plays a vital role in developing multicultural awareness to shape a generation that values differences within the framework of Islamic values of grace for the universe (rahmatan lil'alamin). This research aims to identify the IRE learning materials that integrate multicultural education values in Grade VIII at SMPN 8 Palangka Raya and to analyze the multicultural values contained within those materials. This study employs a qualitative method with data collection techniques using interviews and analyzed using an interactive analysis model. The results of the study indicate that IRE learning at SMPN 8 Palangka Raya integrates multicultural values such as tolerance, justice, and brotherhood to shape students' character. Through materials and methods such as group discussions and stories of the prophets, students are taught to appreciate differences, uphold social justice, and live harmoniously in a pluralistic society. The values of multicultural education taught in the IRE learning materials at SMPN 8 Palangka Raya are highly relevant for building students' character in a diverse society. Values such as tolerance, democracy, religious moderation, egalitarianism, and love for the homeland are integrated into learning to form an inclusive attitude and respect for differences.